Problems of Legal Regulation and State Policy Measures Related to Nature Management in the Framework of Achieving the SDGs: Examples from Russia and Kazakhstan - Sopykhanova, A.; Maytanov, A.; Kiseleva, A.; Zhamiyeva, R. (Sustainability, 2023)
The paper considers the problems of legal regulation and environmental policy in Russia and Kazakhstan related to the achievement of the UN Sustainable Development Goals. The focus of this study is in the plane of studying the features of legislative regulation and the arrangement of political priorities in the two countries in order to determine their similarities and differences. The study intends to assess the current state of the legislative regulation of the Russian Federation and the Republic of Kazakhstan in the context of achieving individual SDGs. Taking into account the object of this study, the assessment of the readiness of countries to achieve the SDGs is carried out within the framework of such criteria as: (1) the current state of the relevant legislation in the field of environmental protection and natural resource management and the analysis of legislative regulation in terms of adaptability to achieve the SDGs, and (2) the role of programmatic-strategic documents in areas corresponding to the SDGs, covering environmental protection and natural resource management. A study of the experience of the Russian Federation gives grounds to say that the fragmented and inconsistent approaches enshrined in policy documents and Russian regulatory legal acts regulating nature management cause duplication of certain provisions of regulatory legal acts. Both Russian and Kazakhstani legislators avoid the universal application of the concept of “sustainable development goals” as a separate category in lawmaking, reserving the right to interpret this term at their own discretion. Formally, in the legislation and strategic and program documents of both countries there is no normative binding justifying the focus on achieving the SDGs, or tools for achieving them. However, on the part of Kazakhstan, strategic documents and national laws and regulations governing sustainable resource management are less diversified and more consistent with each other. The study gives grounds to say that in view of the presence in the Russian legal field of many inconsistent laws and political documents, harmonization of strategic documents related to the achievement of the SDGs is an urgent issue for the Russian Federation. For RK, this problem is less obvious. At the regulatory level, the instruments for achieving the UN SDGs and their indicators are not enshrined in the laws of both countries. References to the defining role of the UN SDGs are absent both in the text of the strategic documents of the Russian Federation and the Republic of Kazakhstan.
Keywords: environmental management policy; global climate change; Kazakhstan; laws; regulations; natural resource management; Russia; sustainable development strategies